Ischemic optic neuropathies: Current concepts - Ajay D Patil; Valerie Biousse; Nancy J Newman (Annals of Indian Academy of Neurology, 2022)
Ischemic optic neuropathy (ION) is the term ascribed to optic nerve disease that is the result of a transient or permanent interruption of the blood supply to any portion of the optic nerve. Anterior ischemic optic neuropathy (AION) refers to ischemia of the optic nerve head, whereas posterior ischemic optic neuropathy (PION) indicates ischemia of the posterior optic nerve. IONs are primarily classified as arteritic ION and non-arteritic ION. A subset of ION that occurs around the time of surgery is termed peri-operative ION. These phenomena will be discussed as distinct entities.